Effect of varieties and planting geometry on growth, yield and profitability of Kharif mungbean [Vigna radiata (L.) Wilezek] in southern Afghanistan - Ibrahimi, Faizrahman; Rana, K.S.; Choudhary, Anil K.; Dass, Anchal; Ehsan, Qudratullah; Noorzai, Amin Ullah (Annals of Agricultural Research, 2017)
An experiment was conducted at Tarnak Farm of Afghanistan National Agricultural Sciences and Technology University (ANASTU), Kandahar, Afghanistan during Kharif 2015 to assess the performance of mungbean varieties viz. Mai-2008, Mash-2008, NM-98 and local cultivar ’Kunduzy’ in combination with 3 planting geometries (20Ã—10, 30Ã—10, and 40Ã—10 cm) under semi-arid conditions of Kandahar. It was revealed that mungbean varieties and planting geometries showed significant differences for growth, morpho-physiological and yield parameters. Mash-2008 exhibited highest seed yield (2031 kg haâ€“1) while Kunduzy led to lowest seed yield (1297 kg haâ€“1). Mash-2008 yielded 7.8, 33 and 56% higher than Mai-2008, NM-94 and ’Kunduzy’, respectively. Planting geometry of 30Ã—10 cm exhibited higher seed yield (1898 kg haâ€“1) followed by 20Ã—10 cm (1641 kg haâ€“1). Mash-2008 produced maximum straw yield while ’Kunduzy’ produced minimum straw yield. Highest gross (AFN 86665 haâ€“1) and net returns (AFN 67672 haâ€“1) and B: C ratio (4.56) were observed in Mash- 2008. Among planting geometries, maximum gross and net returns and B: C ratio were observed in 30Ã—10 cm spacing followed by 20Ã—10 cm and 40Ã—10 cm spacing. Overall, Mash-2008 under planting geometry of 30Ã—10 cm led to higher growth, crop productivity and profitability followed by Mai- 2008 at 30Ã—10 cm spacing in Kharif mungbean crop under semi-arid conditions of Afghanistan.